Academic mothers as "ideal workers" in both the US and Finland. Issue 4 (18th April 2020) - Unknown
Abstract : Purpose: The purpose was to explore how women academics in Finland and the US experience academic motherhood, how they time their pregnancy, and the ways in which the 10;different policy environments shape their decisions and experiences. Design/methodology/approach: The interviewer collected data through 10;semi-structured, long interviews with 67 academic mothers, 33 in Finland and 34 in the US. They were recorded and transcribed, then analyzed for themes. Findings: In Finland, the insecurity of fixed-term contracts and the growing influence of the neoliberal "ideal worker" concept influenced decisions despite the generous work-family policies of the Government. In the US, meanwhile, concerns about age-related infertility had a bigger impact than career risks. One thing the US and Finnish women had in common was a feeling of being under pressure to maintain their presence at work while on maternity leave. Originality/value: Cross-cultural studies of academic motherhood are rare. The choice of Finland and the US was instructive because of the different work-family policies in place. Finland has some of the most generous family leave policies in the world, whereas the US has not yet seen a federal, paid maternity leave policy.